Pengaruh Bahan Baku, Management Supplay Chain, Dan Modal Terhadap Pendapatan Pedagang Sate di Kecamatan Abiansemal Kabupaten Badung Tahun 2020 - Putra, Putu Cipta Perdana; Devi, Sunitha (Universitas Pendidikan Ganesha, 2020)
This research aims to determine the effect of raw materials, supply chain management, and capital on the income of satay traders in Abiansemal District, Badung Regency in 2020. The observation used is quantitative research using data obtained from questionnaires and measured using a Likert scale. The population of this research is 93 satay traders in the Badung Regency as many as 93 traders. The sampling technique used was purposive sampling technique, so that 33 satay traders were obtained as samples. The analysis technique used in this study is multiple linear regression analysis using SPSS version 20.0 IMB. The results of this risset show that raw materials, supply chain management, and capital have a positive effect on the income of satay traders.